The Trouble with SMS Two-Factor Authentication. - Kugler, Logan (Communications of the ACM, 2019)
The article discusses challenges and vulnerabilities associated with the use of SMS two-factor authentication on smartphones to secure online accounts, including SIM card swapping by hackers and SMS-based phishing.